1996
DOI: 10.1002/(sici)1098-2264(199606)16:2<106::aid-gcc4>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Clonal origin of trisomy for chromosome 7 in the epithelial compartment of colon neoplasia

Abstract: In this study, we demonstrated the clonal origin of trisomy for chromosome 7 in epithelial cells of colon neoplasia. By using the double‐target fluorescence in situ hybridization (FISH) technique in frozen tissue sections that were also immunostained for keratin and vimentin, ratio analysis of FISH signals for chromosomes 7 and 17 could be performed in epithelial (cytokeratin‐positive) or stromal (vimentin‐positive) areas. The data demonstrated that trisomy for chromosome 7 is found exclusively in the epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…In CRC and colorectal adenoma, amplification of chromosome 7p (Ch.7p) occurs frequently . Recently, our multiregional genomic analysis showed that the amplification of Ch.7p occurs in all regions of an individual tumor .…”
Section: Introductionmentioning
confidence: 99%
“…In CRC and colorectal adenoma, amplification of chromosome 7p (Ch.7p) occurs frequently . Recently, our multiregional genomic analysis showed that the amplification of Ch.7p occurs in all regions of an individual tumor .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to DNA-based tests such as CGH and LOH analysis, which require the use of samples highly enriched for tumor cell content, FISH visually identifies the chromosomal aberrations on metaphase chromosome or interphase nuclei of the individual cells. This approach has been used to identify colorectal carcinogensis (27, 28), bladder cancer (29), head neck (30), lung carcinoma (31), cervical cancer (32-34), and germ cell tumors (35). …”
Section: Discussionmentioning
confidence: 99%
“…H-J Visualization of the intermediate filament protein vimentin (two-step blue β-Gal-BCIG detection) together with biotinylated centromere 1 and digoxigeninlabeled centromere 7-specific probes [H, I; one-step HRP-DAB and two-step (H) APase-fast red or (I) HRP-TMB detection, respectively], or biotinylated centromere 1, digoxigenin-labeled centromere 7 and fluorescein-labeled centromere 17-specific probes (J; one-step HRP-DAB, and two-step APase-fast red and HRP-TMB detection, respectively). [After Speel et al 1994a (A, C, F, G), 1994b (H-J); Herbergs et al 1996aHerbergs et al (B), 1996b. Images C, F-J are reproduced with permission of the Journal of Histochemistry and Cytochemistry, and images B, D, E are courtesy of J.…”
Section: Combination Of Immunocytochemistry (Icc) and Ishmentioning
confidence: 96%
“…Although this can be achieved by comparing the results of ICC and ISH carefully on serial sections, there are now a variety of protocols available to combine ICC and ISH efficiently on the same cell preparation or tissue section. These procedures have been utilized to simultaneously demonstrate the presence of mRNA and its protein product in one cell (see, for example, Larsson and Hougaard 1991;Harper et al 1992;Heppelmann et al 1994;Dirks 1996), to immunophenotype cells containing a specific chromosomal aberration or viral infection (see, for example, Porter et al 1990; Van den Berg et al 1991;Kibbelaar et al 1992;Strehl and Ambros 1993;Weber-Matthiesen et al 1993a;Zheng et al 1993;Bridge et al 1994;Knuutila et al 1994;Leger et al 1994;Robben et al 1994;Speel et al 1994a,b;Herbergs et al 1996a), to facilitate evaluation of chromosomal aberrations in tissue sections by nuclear border staining of lamins prior to ISH (see, for example, Herbergs et al 1996b), to determine cytokinetic parameters of tumor cell populations that are genetically or phenotypically aberrant (see, for example, Schutte et al 1987;Balazs et al 1991;Van Dekken et al 1991;Ffrench et al 1994;Speel et al 1994a), and to study the three-dimensional organization of the cell nucleus (see, for example, Matera and Ward 1993;Zirbel et al 1993;Junera et al 1995;Xing et al 1995;Jolly et al 1997).…”
Section: Combination Of Immunocytochemistry (Icc) and Ishmentioning
confidence: 99%
See 1 more Smart Citation